GEOCHEMICAL INVESTIGATIONS TO EXPLAIN IODINE-OVERABUNDANCES IN ANTARCTIC METEORITES - Heumann K.G.; Gall M.; Weiss H. (My University, 1987)
Iodine, bromine, and chlorine concentrations were determined in different Antarctic meteorite specimens (eucrites, high-iron and low-iron chondrites) with isotope dilution mass spectrometry. In all Antarctic meteorites I-overabundances have been analysed compared with the concentrations for non-Antarctic meteorites of the same class. Half of the Antarctic specimens show especially high concentrations of more than 1 μ/g. A similarly high enrichment effect in Antarctic meteorites was not found for Br and Cl, but smaller Cl excesses could be observed in some eucrites and high-iron chondrites.By analysing different types of Antarctic rocks, a significant decrease of the I concentration—but not of the Br and Cl concentration-was determined from the surfaces to the centers of the rocks. This shows that atmospheric I compounds interact with the surfaces of Antarctic rocks and, therefore, with those of Antarctic meteorites as well. Analyses of atmospheric halogens show that the gaseous compound CH3I is probably responsible for the I-overabundance in Antarctic meteorites and rocks. Chloride and bromide are found in particles derived from sea-spray in Antarctic aerosols. Deposition of halogens in Antarctic snow near the coast shows I/Cl ratios 10–190 higher than the average value for seawater. The corresponding Br/Cl ratios are in the same range as seawater. On the basis of our results and of other reported data we construct a preliminary hypothesis for a geochemical I cycle in Antarctica, taking into consideration long-distance and short-distance transportation of different I compounds from the coast to inland Antarctica. …